Reviews. Issue 1 (2nd January 2021) - Moreno, Hayley; Baker, Heather; Parang, Elizabeth; Wilson, Robert T.
Abstract: Heather Baker reviews Emergency Preparedness for Libraries, Second Edition ; Elizabeth Parang reviews Leading Change in Academic Libraries ; Robert T. Wilson reviews Makerspace and Collaborative Technologies, a LITA Guide.